Thanking and responding to thanks in American English - Barron, Anne (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Speech act realisations in textbooks are commonly based on authors’ intuitions. Thus, they frequently do not mirror the conventions of actual language use. The present lesson takes an inductive approach and encourages learners themselves to analyse realizations of expressions of gratitude and responses to expressions of gratitude as they are used in American English. To this aim, the freely available Michigan Corpus of Academic Spoken English (MICASE) is employed. Learners are guided to identify formulaic sequences used to express gratitude in American English (e.g. thanks a lot, thanks for + verb), to observe the contexts of use of different expressions of gratitude and to examine how expressions of gratitude are responded to both verbally and non-verbally in American English.
Language patterning and contextual appropriateness